Analisis Kinerja Jaringan Irigasi Pada Daerah Irigasi Plunturan Kabupaten Ponorogo - Mulyadi Retang, Mus; Noorvy Khaerudin, Dian; Suhudi; Dinar Rahma, Pamela (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2023)
Plunturan Village, Pulung District, Ponorogo Regency, there is the Plunturan Irrigation Area, which has an operational area of 18 hectares. Water needs for agriculture require strong irrigation infrastructure. The aim of this research is to assess the effectiveness and efficiency of the irrigation network assets in the Plunturan Irrigation Area. In accordance with the Performance of Electronic Asset Management and Water Systems (e-PAKSI) and PUPR Ministerial Regulation Number 12/PRT/2015, this research uses quantitative descriptive techniques. We used e-PAKSI to survey people in the secondary to tertiary stages of the irrigation network to get information on the irrigation system performance index (IKSI) and the management of irrigation assets (PAI). Eleven canal sections and fourteen irrigation facilities, each of which has unique characteristics, form the irrigation network of the Plunturan Irrigation Area, according to PAI data. The condition value of canal assets is 72.12%, and the condition value of irrigation building assets, if considered together, is included in the medium condition group. The channel asset condition value is known to be 56.24%. Performance of the irrigation network of the Plunturan Irrigation Area, both quantitatively and qualitatively. With a performance score of 63.79%, the primary irrigation system is classified as requiring quick maintenance, while the tertiary irrigation system is in the same category with a performance score of 53.42%. The findings of the IKSI data study strengthen this conclusion. If irrigation operation and maintenance services are poor, the irrigation network will not be well maintained. Maintenance responsibilities include performing routine and sporadic maintenance as well as minor and major repairs and upkeep.